An examination of the determinants of corporate ownership structure in an emerging market context / Omar Al Farooque - Al Farooque, Omar (Universiti Teknologi MARA Cawangan Selangor, 2010)
Using historical data, this study investigates the determinants of corporate ownership structure in an emerging economy in the context of two different but interactive policy directions (or reversal of policy) of market regulators. It also highlights the effectiveness of importing Anglo-Saxon governance models to emerging markets in the name of promoting ‘good corporate governance’. Based on established literature, a single equation approach is applied on a pooled sample of 490 observations listed on the Dhaka Stock Exchange over eight years to identify whether measures of corporate performance and other governance factors do contribute in shaping ownership structure. The findings indicate that while there is support for reducing board ownership level, there is no such support for reducing Top 1 shareholder’s ownership level. It suggests that the ownership restriction imposed by the SEC is unjustified and detrimental to firm performance/growth in emerging countries like Bangladesh. The study has implications for stakeholders, regulators and policy makers to revisit their attempts to limit the founder-family ownership holdings.